Accuracy of HRP2 RDT (Malaria Antigen P.f®) compared to microscopy and PCR for malaria diagnosis in Senegal. (1st July 2013) - Faye, Babacar; Nath-Chowdhury, Milli; Tine, Roger Clément; Ndiaye, Jean Louis; Sylla, Khadime; Camargo, Fabio Wasquez; Martel, Nathalie; Foly, Kouakou; Lô, Aminata Collé; Abiola, Annie; Sow, Doudou; Ndiaye, Magatte; et al.
Abstract : Rapid diagnosis tests (RDTs) allow for the confirmation of malaria diagnosis. In Senegal, RDTs detecting HRP2 have been adopted in 2008 for malaria diagnosis. However, the sustainability of this strategy requires adequate and regular quality control. PCR on DNA extracted in nitrocellulose band of RDTs enable quality control. A RDT ( Malaria Antigen P.f ®) and a thick smear were performed on patients with suspected malaria. DNA was extracted from the nitrocellulose band of RDTs to which a non-specific PCR and a specific PCR were applied. The results of the RDT were compared with those obtained from the thick smear and the PCR to measure sensitivity, specificity as well as positive and negative predictive values. For 81·6% of the 273 patients involved, the thick smear was positive. Rapid diagnosis tests were positive for 85·7% of the patients. Non-specific PCR was positive on 87·9% of RDTs. Plasmodium falciparum was found in 99·5% of patients and Plasmodium ovale appeared in only 0·4% of patients. Sensitivity of the Malaria Antigen Pf® RDT in relation to thick smear and to PCR was 98·2% and 97·1% respectively. Quality control with PCR on the nitrocellulose band performed several months after it was used confirms its adequate level of sensitivity. The collection and screening of DNA present in already used RDT is a good means of quality control for this tool. It is also a relevant alternative to the molecular approach in the context of a reduction in the transmission of malaria.